2005
DOI: 10.1007/s00330-004-2600-1
|View full text |Cite
|
Sign up to set email alerts
|

Contrast media: interactions with other drugs and clinical tests

Abstract: Many patients with multiple medical problems who are receiving a variety of drugs are investigated with imaging techniques which require intravascular contrast media. The Contrast Media Safety Committee of the European Society of Urogenital Radiology therefore decided to review the literature and to draw up simple guidelines on interactions between contrast media and other drugs. An extensive literature search was carried out and summarized in a report. Based on the available information, simple guidelines hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Our findings, while consistent with studies examining clinical variables such as functional outcome, do not necessarily contradict the findings of other in vivo and in vitro studies that demonstrate an effect of contrast on tPA-induced thrombolysis 3–6,13 . Previous research has demonstrated that increasing concentrations of tPA reduce the impairment of thrombolysis by contrast.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings, while consistent with studies examining clinical variables such as functional outcome, do not necessarily contradict the findings of other in vivo and in vitro studies that demonstrate an effect of contrast on tPA-induced thrombolysis 3–6,13 . Previous research has demonstrated that increasing concentrations of tPA reduce the impairment of thrombolysis by contrast.…”
Section: Discussionsupporting
confidence: 91%
“…IRCM rats did exhibit lower CBF than control animals, and IRCM+heparin rats exhibited reduced CBF compared with heparin-only animals. IRCMs are known to have paradoxical prothrombotic, anticoagulant, and fibrinolytic effects 3238 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Krause et al [ 8 ] stated also that clots formed in the presence of iopromide were unstable and did not absorb the contrast agent [ 8 ]. It has also been reported that ionic contrast media inhibit both the intrinsic and extrinsic coagulation pathway at several level and may act as direct inhibitors of thrombin production [ 9 ]. In the case of erythrocytes, it was found that CAs may contribute to the changes in their morphology which as a consequence can change their capacity for oxygen delivery and pH buffering [ 10 ].…”
Section: Introductionmentioning
confidence: 99%